Prostaglandin E1 Protects the Peripheral Nerve in Diabetics through Preventing Vascular Permeability Changes - Mo, Feifei; Hu, Guotao; Liu, Wei; He, Li; Wang, Hailan (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective The aims of this study were to investigate the effects of the vasodilator prostaglandin E1 on microvascular permeability, the expression of vascular endothelial growth factor (VEGF), as well as the structural and functional changes of the peripheral nerve in diabetic rats.Methods Streptozotocin-induced diabetes mellitus were randomly divided into two groups and intraperitoneally received, once daily, an injection of prostaglandin E1 at 1.6 μg/kg in normal saline or the same volume of normal saline (diabetic control), respectively. Six rats were randomly selected as normal controls.Results Diabetic controls exhibited a significant increase in the tail flick threshold temperature, water content of the sciatic nerve, serum VEGF level, and VEGF level in the sciatic nerve; in addition, a decrease in the sciatic nerve conduction velocity (NCV) was observed, compared with normal rats (P<0.01). Treatment with prostaglandin E1 resulted in similar changes but at a slower rate than in those without treatment. Diabetic control rats also showed histological and ultrastructural abnormalities of the sciatic nerve, whereas prostaglandin E1-treated rats exhibited similar but less severe injury. The serum VEGF level was negatively correlated with the sciatic NCV (r=−0.932, P<0.01) and positively correlated with the tail flick threshold temperature (r=0.835, P<0.01) as well as the water content of the sciatic nerve (r=0.901, P<0.01).Conclusion Prostaglandin E1 could protect the peripheral nerve by improving sciatic nerve function, reducing the VEGF level, and decreasing the vascular permeability. This study provides an experimental proof that prostaglandin E1 has potential benefits in improving DPN in early stage.
Keywords: prostaglandin E1; diabetic rats; vascular endothelial growth factor; vascular permeability; peripheral nerve